1997
DOI: 10.1097/00007632-199705150-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Low Back Pain Among Children and Adolescents

Abstract: Low back pain is a relatively common complaint at adolescence. In addition, a significant part of the pains are recurrent or chronic already with 14-year-old adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(90 citation statements)
references
References 27 publications
8
77
0
5
Order By: Relevance
“…These results are in agreement with the results of Ehrmann-Feldman, who found a 1-year cumulative incidence of LBP of 17.2% [10]. A significant proportion of adolescents report recurrent or chronic pain [4,21]. In Finland, Zitting et al studied a large cohort of subjects (about 12,000) born in 1966, focusing on hospital admissions due to lumbar disc diseases.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with the results of Ehrmann-Feldman, who found a 1-year cumulative incidence of LBP of 17.2% [10]. A significant proportion of adolescents report recurrent or chronic pain [4,21]. In Finland, Zitting et al studied a large cohort of subjects (about 12,000) born in 1966, focusing on hospital admissions due to lumbar disc diseases.…”
Section: Introductionsupporting
confidence: 83%
“…From this study we can establish that there are few clinical signs that can help to single out school children with LBP. studies in different countries have shown that the prevalence of non-specific LBP among adolescents is close to the figures well known for adults [1,5,13,14,16,17,19,21,23]. The epidemiology of LBP and the associated factors among these age groups have been reviewed by different authors [2,3,7,9,22].…”
Section: Introductionmentioning
confidence: 97%
“…87, 138, 209 In cross-sectional studies, activity and prevalence of back pain takes on a “U” shaped function with back pain increased at the sedentary and higher activity end. 287, 307 However, in longitudinal studies, the relationship between modifying physical activity and back pain prevalence has not been well-established. 166, 257 As is the case in adults, psychological and psychosocial factors are commonly increased in children with low back pain and there is some evidence that such factors can predict future onset of low back pain.…”
Section: Clinical Guidelines: Impairment/function-based Diagnosismentioning
confidence: 99%
“…Keywords Adolescents Á Low-back pain Á Physical activity Á Prevention Á Health promotion Background Low-back pain (LBP) is frequent among schoolchildren [1][2][3][4][5][6][7][8]. The occurrence increases with age, especially in the early teen-years [1, 2, 9, 10] so that, by age 14-17, 11-71% will have experienced at least one episode of LBP [1][2][3][4][5][9][10][11].…”
mentioning
confidence: 99%
“…Recurrent LBP during childhood seems to occur among 5-19% of all children [4,5,9], and LBP in childhood may be a forerunner of LPB in adult life [12]. Findings concerning an association with gender have been ambiguous [1,2,5,[7][8][9][10][11][12][13][14].…”
mentioning
confidence: 99%